FACTORS AFFECTING THE INCOME BASE OF COMMERCIAL BANKS IN UZBEKISTAN (World Economics and Finance Bulletin, 2023)
The study covers the main aspects affecting the financial performance and stability of commercial banks. This study analyzes various external and internal factors such as macroeconomic conditions, market conditions, innovative technologies and regulation that affect the profitability and earnings composition of commercial banks. The study also explores the importance of effective risk and credit management for banks to ensure a stable revenue base. The results of this study can be useful to both the banking industry and regulatory authorities by helping to better understand and manage the factors affecting the profit base of commercial banks and to develop appropriate strategies to ensure sustainable financial development.